2019
DOI: 10.1111/hsc.12926
|View full text |Cite
|
Sign up to set email alerts
|

Formal and informal support and counselling for embryo donation and receipt: An Australian qualitative study

Abstract: Despite growing numbers of people engaging in embryo donation for the purposes of family building, public access to information about the process may be limited. As such, support and counselling – both formal (i.e. through clinics) and informal (i.e. through online communities) – can play an important role in information provision. This article draws on a sub‐sample of nine people from a qualitative study of embryo donation and receipt in Australia undertaken in 2017–2018. Themes developed suggest that formal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…This study confirms findings from previous research that highlighted the positive aspects of counselling, such as information giving (Hammarberg et al, 2008; Riggs & Bartholomaeus, 2020; Yee et al, 2007), or discussion of the potential implications for the individual donor (Hogan et al, 2021). Person‐centred care can enhance the overall experience of egg donation and has been argued as needing to be foregrounded during counselling (Hogan et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study confirms findings from previous research that highlighted the positive aspects of counselling, such as information giving (Hammarberg et al, 2008; Riggs & Bartholomaeus, 2020; Yee et al, 2007), or discussion of the potential implications for the individual donor (Hogan et al, 2021). Person‐centred care can enhance the overall experience of egg donation and has been argued as needing to be foregrounded during counselling (Hogan et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…However, many of the participants in this study felt that they had already received much of the information they needed from other staff they encountered at their clinic or agency, before having the counselling. Therefore, it was unclear for many participants what role the counsellor had in their treatment process, and as other studies have also found, this made the counselling feel, for some, like a "tick box" exercise, rather than one that was aimed at exploring their needs in depth (Riggs & Bartholomaeus, 2020). This may be exacerbated by the multiple purposes of counselling in fertility treatment, which can be focussed on both the consideration of "implications" and for providing therapeutic or emotional support (BICA, 2019).…”
Section: Discussionmentioning
confidence: 99%